Evaluating Floor-by-Floor Material Consumption and Cost Efficiency for the Superstructure of Princeton Boutique Living Apartment, Medan, Indonesia - Bintarto Purwo Seputro; Samsudin Silaen (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study investigates the floor-by-floor material consumption and cost efficiency of the superstructure in the Princeton Boutique Living Apartment, a mixed-use high-rise building located in Medan, Indonesia. The research employs a quantitative approach, utilizing construction shop drawings and adhering to national regulatory standards to estimate the volume and cost of concrete, reinforcement, and formwork across floors 1 to 15. AutoCAD was used for accurate dimension extraction, while Microsoft Excel facilitated calculations and budgeting. The findings reveal substantial variation in material requirements, particularly on lower floors that accommodate facilities such as gyms and pools, leading to increased structural demands. The total estimated cost for the upper structure is approximately IDR 25.97 billion. These results underscore the importance of detailed, floor-specific estimation in high-rise projects and highlight the need for integrative digital tools in construction cost management. The study contributes to improving budget accuracy and material planning in future developments with similar design complexity.